2005
DOI: 10.1016/j.chembiol.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Engineering of E. coli Galactokinase as a First Step toward In Vivo Glycorandomization

Abstract: In vitro glycorandomization is a rapid chemoenzymatic strategy to diversify complex natural product scaffolds. The glycorandomization sugar activation pathway is dependent upon the efficient construction of diverse sugar-1-phosphate libraries. In the context of the previously evolved GalK Y371H "gatekeeper" mutation, the active site M173L mutation described herein presents a kinase with remarkably broadened substrate range to include 28 diverse natural and unnatural sugars. Among these new substrates, 6-azido-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 32 publications
3
61
1
2
Order By: Relevance
“…In humans, deficiencies of this enzyme can result in type II galactosaemia (MIM 230200), the main symptom of which is cataract development (Holton et al, 2001). Recently, Escherichia coli galactokinase has been utilized via a directed-evolution approach to create natural and unnatural sugar 1-phosphates in a process of glycorandomization, with the aim of enhancement of drug-discovery efforts (Hoffmeister et al, 2003;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, deficiencies of this enzyme can result in type II galactosaemia (MIM 230200), the main symptom of which is cataract development (Holton et al, 2001). Recently, Escherichia coli galactokinase has been utilized via a directed-evolution approach to create natural and unnatural sugar 1-phosphates in a process of glycorandomization, with the aim of enhancement of drug-discovery efforts (Hoffmeister et al, 2003;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During these studies, it was observed that E. coli GalK M173L displayed moderate D-glucose activity (27). The equivalent residue in the yeast enzyme (Met-216) is located in the active site (next to Asp-217 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to change or broaden the substrate specificity range of galactokinases have been undertaken using the Escherichia coli enzyme through the application of in vitro glyco-randomization (26,27). During these studies, it was observed that E. coli GalK M173L displayed moderate D-glucose activity (27).…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested in the case of galactokinase (EC 2.7.1.6), where alterations to the sequence of a β-sheet structure distant from the active site resulted in a broader range of substrates being accepted and processed by the enzyme (19,20,(55)(56)(57).…”
Section: Towards An Alternative Paradigm For Protein Engineeringmentioning
confidence: 99%